2022
DOI: 10.1088/1741-2552/ac6f81
|View full text |Cite
|
Sign up to set email alerts
|

Semantic fMRI neurofeedback: a multi-subject study at 3 tesla

Abstract: Objective. Real-time fMRI neurofeedback is a non-invasive procedure allowing the self-regulation of brain functions via enhanced self-control of fMRI based neural activation. In semantic real-time fMRI neurofeedback, an estimated relation between multivariate fMRI activation patterns and abstract mental states is exploited for a multi-dimensional feedback stimulus via real-time representational similarity analysis (rt-RSA). Here, we assessed the performances of this framework in a multi-subject multi-session s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…As NF methodologies continue to evolve, focusing on the process of regulating affective states, rather than activating specific brain regions, might yield more effective treatments. In this context, the semantic NF approach, which emphasizes navigating positions within the representational state space over focusing on specific brain activities, offers a promising direction for refining training protocols 75, 76 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As NF methodologies continue to evolve, focusing on the process of regulating affective states, rather than activating specific brain regions, might yield more effective treatments. In this context, the semantic NF approach, which emphasizes navigating positions within the representational state space over focusing on specific brain activities, offers a promising direction for refining training protocols 75, 76 .…”
Section: Discussionmentioning
confidence: 99%
“…As NF methodologies continue to evolve, focusing on the process of regulating affective states rather than merely activating specific brain regions might yield more effective treatments. In this context, pattern-based NF approaches such as DecNef 77 , connectome-based neurofeedback 78 , and semantic neurofeedback 79, 80 , which emphasize extracting feedback signals from multivariate brain activation patterns, offer a promising direction for refining training protocols.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of different studies have shown the possible applications of real-time functional magnetic resonance imaging (rt-fMRI) and facilitate the importance of this method (Ciarlo et al, 2022; Lührs et al, 2019; Pandria, Athanasiou, Konstantara, Karagianni, & Bamidis, 2020; Russo, Lührs, Salle, Esposito, & Goebel, 2020; Sorger et al, 2009; Tursic, Eck, Lührs, Linden, & Goebel, 2020; Weber, Ethofer, & Ehlis, 2020; Weiskopf, 2012). The main prerequisite for successful rt-fMRI is the ability to get access to the fMRI data in real-time.…”
Section: Introductionmentioning
confidence: 99%